Left ventricular trabecular complexity for risk stratification of cancer therapy–related cardiac dysfunction in breast cancer - Hesong Shen; Qian Xu; Chunrong Tu; Yangling Peng; Yuhang Xie; Zhiming Miao; Rui Yang; Jiuquan Zhang (MedComm)
Abstract The left ventricular trabecular fractal dimension (LVTFD) derived from cardiac magnetic resonance reflects myocardial trabecular complexity, which is associated with cardiovascular disease risk. Baseline risk stratification of cancer therapy–related cardiac dysfunction (CTRCD) in patients with breast cancer who received anthracycline is a very important clinical issue. In this study, we used the Cox model to derive and validate a new score system based on LVTFD for baseline risk stratification of CTRCD in breast cancer patients receiving anthracycline. We also compare the performance of LVTFD‐based score with the Heart Failure Association‐International Cardio‐Oncology Society (HFA‐ICOS) score using C‐index. This study enrolled 370 participants, of whom 73 participants developed CTRCD. The C‐indices of LVTFD‐based score integrating age, hypertension, previous cardiovascular disease, and maximal apical fractal dimension were higher than those of HFA‐ICOS score for stratifying CTRCD (0.834 vs. 0.642 and 0.834 vs. 0.633, respectively, in derivation and validation cohort). LVTFD‐based score can stratify the CTRCD risk, but HFA‐ICOS score cannot. The above results reveal that the LVTFD‐based score is an alternative method for baseline risk stratification of CTRCD in breast cancer who received anthracycline.